Analisis Wacana Kritis “Hukuman Salah Alamat” pada Acara Mata Najwa - R. Saleh (Balai Bahasa Kalimantan Tengah, 2020)
Mata Najwa is a talkshow program that discusses current issues that occur in Indonesia. One of its episodes was